Computer-Aided Detection of Retinopathy of Prematurity Severity in Preterm Infants via Measurement of Temporal Vessel Width and Angle - Huang, Yo-Ping; Vadloori, Spandana; Kang, Eugene Yu-Chuan; Wu, Wei-Chi (Frontiers in Pediatrics, 2022)
Retinopathy of prematurity (ROP) is a retinal disorder in preterm infants born with a low birth weight and is known to be the leading cause of preventable blindness in children. The early identification of high-risk patients and the early diagnosis and timely treatment of ROP could significantly improve patients' visual outcomes. However, manual screening is both time- and resource-consuming. Telescreening with retinal fundus images has the potential to reduce the burden of ophthalmologists in performing on-site screening. Recently, computer-aided diagnosis using retinal fundus images has made substantial progress and attracted considerable attention from the research community in the diagnosis of eye diseases. Abnormalities of or alterations in the retinal blood vessels may relate to the occurrence and progression of ROP. In this study, we aimed to examine the hypothesis that the severity of ROP may be associated with the angle and width of arteries/veins. We determined the artery-artery and vein-vein angles in the temporal quadrants, including the temporal artery angle (TAA) and temporal vein angle (TVA), computationally under normal conditions and in different stages of ROP. We also estimated the retinal vessel width (temporal artery width (TAW) and temporal vein width (TVW)) by employing the radon transform (RT) method to measure the artery and vein vessel width based on fundus images. Our results revealed a significant decrease in the TAA and TVA and an increase in the TAW and TVW with increasing ROP severity (all P<0.0001). In addition, there was a positive correlation of the TAA with the TVA and the TAW with the TVW (both P<0.0001). There was a negative correlation of the TAA with the TAW (r=-0.162, P=0.0314). These retinal vessel features might be useful in assisting ophthalmologists in the early detection of ROP and its progression.